The Issue Of Business Competition Among Padang Restaurants According To Law Number 5 Of 1999 - Sherinda, Ghea Premarsha; Erniwati, Erniwati; Sakinah, Sakinah (JURNAL HUKUM SEHASEN, 2025)
One of the food businesses that has high competitiveness is Padang restaurants. Padang restaurants are known as delicious restaurants that can adapt to the tastes of the entire community. In the 1950s to 1970s, Padang restaurants experienced rapid growth. Many Minangkabau entrepreneurs opened their businesses in various cities, thus creating business competition. Tight business competition encourages Padang restaurants to continue to improve quality and innovation. However, this competition also poses challenges such as monopolistic practices and unhealthy business competition. The problems in this thesis are the existence of unhealthy competition in the Padang restaurant business and legal settlement efforts that can be taken if a dispute occurs between Padang restaurants. This problem was triggered by a 38-second viral video showing the actions of a number of people removing the "Padang Cuisine" label in Sukadana Village which sells food at prices below market prices, which are only IDR 9,000 per portion. This study uses the Normative research method. The results of the analysis show that the practice of revoking the “Padang Cuisine” label is because the owner of the Padang restaurant in Sukadana Village sells food at a price below the market price, which is only IDR 9,000 per portion. Based on Article 20 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. It can be concluded that what the owner of the restaurant in Sukadana Village did was an act prohibited by Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Because the restaurant sets a price that is very low or below the market price, it is detrimental to other Padang restaurant business owners.